Estudo da influência das condições de ativação térmica do CaO na reação de transesterificação do óleo de soja - Nascimento, Cleuciane Tillvitz do (2015)
The climate changes caused by fossil fuels, associated with brief shortage of oil, have caused a increase search for new renewable sources. Biodiesel is a biofuel that has been used and studied for decades. The most usual method production is the homogeneous catalyst, which has presented disadvantages with respect to biodiesel cost and purity, then, the heterogeneous catalysis has appeared to solve this problems. Calcium oxide (CaO) has been studied as a promising heterogeneous catalyst in the fatty acid esters production, however, some treatments are needed for the CaO exhibit good catalytic activity. Therefore, this work had like a goal, the study of the influences of the thermal activation of CaO in the production of methyl esters of fatty acids (FAME) from soybean oil transesterification. Was performed the study the effects of temperature, time and activation rate of the commercial CaO in the transesterification reaction. At the temperatures studied (300, 500, 700, 900°C), was observed that for a temperature of 500ºC had the best yield (36%) of FAME, using rate and activation time 10°C/min and 5 hours, respectively. For the activation times studied (1, 3, 5 and 7 hours) was observed, a 78% yield of FAME for 1 hour of the activation, using a temperature and heating rate of 500°C and 10ºC/min, respectively. In the study of the activation rate, were used 1, 5, 10 and 15°C/min rates, and was observed that the better yield with 5ºC/min, however, the variation in yield between 1 and 5°C/ min was very low (84-87%) and the difference in rates of 15 - 1°C/min was only 5% in the FAME production . Thus, was determined the condition of 1ºC/min, as best activation rate, taking into account systematic errors in the experiments. Transesterification reactions using CaO without activation (SA) were also performed. The molar ratio of oil/methanol 6:1; 2% by weight catalyst; temperature 64°C and reaction time of 5 hours were use for all transesterification reactions. The characterization of activated and non-activated catalysts were performed by Thermogravimetric analysis (TGA), nitrogen physisorption, Fourier transform infrared spectroscopy (FT-IR) and X-ray Diffraction (XRD). Analysis of XRD and FT-IR for CaO obtained in better thermal activation condition in the range studied, were performed. Contamination of catalysts for CO2 was observed and moisture, but physisorption analysis revealed high pore volume for CaO activated at 500°C, enhancing their activity in the transesterification reaction, moreover, the activation of CaO at 500°C can increase basicity, increasing the FAME conversion. Was determined the production of FAME (%) by gas chromatography and infrared analysis of the ester phase were carried out for the FAME sample obtained of the reaction with CaO activated under optimum conditions, and was observed marked differences in the absorption spectra in relation to the oil soybean, revealing the formation of FAME. The study of the effect of thermal activation conditions of commercial CaO in the transesterification of soybean oil don’t exists. The results helped determine the value of influential variables in the catalytic ability of the catalyst